2020
DOI: 10.32604/phyton.2020.010952
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Barcoding of Some Medicinal Plant Species in Saudi Arabia Using rbcL and matK Genes

Abstract: In the Kingdom of Saudi Arabia (KSA), thousands of plants are considered to have therapeutic value. The ambiguous use of identification mainly morphological characteristics of many plants has resulted in the adulteration and displacement of plant products which undermine their therapeutic value and weak documentation of plant resources. The aims of this study were therefore to evaluate genetic variability and explore the phylogeographic architecture for Saudi medicinal plant samples using rbcL and matK genes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The ideal locus for DNA barcoding of plants remains debatable since some loci are efficient for some taxonomic groups and the species discrimination of these genes varies among plant species. Although the result of the matK gene phylogenetic tree is not sufficiently accurate to differentiate plants at species level, the rbcL gene-based data would help with this deficiency, this is in accordance with the study by Dong et al (2012) that one DNA barcoding marker is not enough to obtain sufficiently accurate and specific identification results (Dong et al, 2012), so matK and rbcL must be used as dual DNA barcoding procedures (Alasmari, 2020).…”
Section: Phylogenetic Treesupporting
confidence: 59%
See 1 more Smart Citation
“…The ideal locus for DNA barcoding of plants remains debatable since some loci are efficient for some taxonomic groups and the species discrimination of these genes varies among plant species. Although the result of the matK gene phylogenetic tree is not sufficiently accurate to differentiate plants at species level, the rbcL gene-based data would help with this deficiency, this is in accordance with the study by Dong et al (2012) that one DNA barcoding marker is not enough to obtain sufficiently accurate and specific identification results (Dong et al, 2012), so matK and rbcL must be used as dual DNA barcoding procedures (Alasmari, 2020).…”
Section: Phylogenetic Treesupporting
confidence: 59%
“…Ho et al (2021) also reported that the discriminating abilities of the matK and rbcL genes in jewel orchid plants showed a different level of efficiency, the rbcL gene was considered to have better discriminating power than the matK gene alone or the rbcL+matK gene combination. According to Alasmari (2020) the separability of the matK gene to differentiate between species is not always reliable, because in their study, only 2 samples of the 4 sequences tested could be identified correctly at the species level. The ideal locus for DNA barcoding of plants remains debatable since some loci are efficient for some taxonomic groups and the species discrimination of these genes varies among plant species.…”
Section: Phylogenetic Treementioning
confidence: 99%
“…DNA barcoding strategies were recruited successfully for different applications in the Middle East, including both plants and animal subjects [26][27][28]. Recently, selected medicinal plant species in Saudi Arabia and the United Arab Emirates were barcoded [29,30]. Moreover, an effective barcode tool was developed to discriminate between different wheat species in Egypt [18].…”
Section: Discussionmentioning
confidence: 99%
“…Two chloroplast genes are commonly used for the analysis; the matK and rbcL are the best gene loci for analyzing relationships in plants [21]. The locus of rbcL can be recognized at the genus and family levels, while matK is the variable portion of the coding for species confirmation [22][23][24]. They have been proposed as the primary plant barcode regions by the committee Barcode of Life (CBOL) [25] consortium [26].…”
Section: Introductionmentioning
confidence: 99%